Magnetic therapy fabric containing heating polyamide fibers and preparation method and application thereof

By preparing additives containing graphene oxide and iron tetraoxide and blending them with nylon 66 resin, heating nylon fibers are prepared by grafting reaction and spinning technology, the problems of insufficient performance of heating and magnetic nylon fibers in the prior art are solved, and the far-infrared heating, magnetic therapy, antibacterial and antistatic properties of the fabric are improved.

CN119749002AActive Publication Date: 2025-04-04SHANTOU MODERN GARMENT CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510258410.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-06
Publication Date
2025-04-04
Estimated Expiration
2045-03-06

AI Technical Summary

Technical Problem

In the prior art, the heating, magnetic therapy and antistatic properties of nylon fibers need to be improved.

Method used

By preparing an additive containing the far-infrared heating material graphene oxide and the magnetic material iron tetroxide, it is blended with nylon 66 resin, and grafting reaction is carried out under microwave radiation conditions to improve dispersion uniformity. Then, heat-generating nylon fibers are prepared by spinning technology and spun into fabrics through knitting process, and finally, the antibacterial and antistatic properties are improved by finishing liquid treatment.

Benefits of technology

The far-infrared heating performance, magnetic therapy performance, antibacterial performance and antistatic properties of nylon fabrics have been improved, significantly improving the warmth and health functions of the fabrics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119749002A_ABST
    Figure CN119749002A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of fabrics, in particular to a magnetic therapy fabric containing heating polyamide fibers and a preparation method and application of the magnetic therapy fabric. The magnetic therapy fabric containing the heating polyamide fibers comprises the inner-layer fabric and the outer-layer fabric, an air layer is formed through the gap between the two layers of fabric to improve the heat preservation performance of the fabric, the fabric is made of the polyamide fibers and is good in wear resistance, and the magnetic therapy fabric is good in heat preservation performance by adding the auxiliaries. The auxiliary agent comprises the components of a far infrared heating material graphene oxide and magnetic materials ferroferric oxide and alkyl quaternary ammonium salt, so that the far infrared heating performance and the magnetic therapy performance can be realized, and meanwhile, the antistatic performance and the antibacterial performance can be improved; the chinlon fabric is subjected to finishing modification treatment, and the antibacterial performance, the antistatic performance and the moisture absorption performance of the chinlon fabric can be further improved. The magnetic therapy fabric containing the heating polyamide fibers is widely applied to the field of textiles such as health-care clothes and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fabrics, and in particular to a magnetic therapy fabric containing heating nylon fibers, and a preparation method and application thereof. Background Art

[0002] Nylon, commonly known as nylon, has excellent wear resistance and moisture absorption and is widely used in the fabric field. With the development of science and technology, people have higher and higher requirements for clothing, such as far-infrared heating performance. By adding far-infrared substances, it can absorb far-infrared rays in sunlight and convert them into its own heat energy, increase the skin surface temperature, and have a good warming effect. In addition, textiles with magnetic therapy functions are gradually gaining attention.

[0003] Chinese patent CN111778581B discloses a far-infrared heating and weather-resistant graphene nylon yarn. The graphene nylon yarn is made by melt spinning polyamide fiber and graphene fiber. The addition of graphene fiber can achieve far-infrared heating of nylon yarn. However, polyamide fiber and graphene fiber are physically blended, and there is a problem of uneven dispersion, and the far-infrared heating performance needs to be improved. Chinese patent application CN108385190A discloses a nylon fiber with magnetic therapy health care function. Nylon fiber is made by melt spinning magnetic therapy masterbatch and nylon 6 slices. The magnetic therapy masterbatch and nylon 6 are physically blended, and there is a problem of uneven dispersion, and the magnetic therapy function needs to be improved. In addition, nylon has the problem of easy static electricity generation, and it is necessary to improve the antistatic performance of nylon fiber. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides a magnetic therapy fabric containing heat-generating nylon fiber to solve the problem that the heat-generating, magnetic therapy and anti-static properties of the heat-generating and magnetic therapy nylon fiber in the prior art need to be improved.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows: a method for preparing a magnetic therapy fabric containing heating nylon fiber, comprising the following steps: Step 1, adding N,N-dimethyl-1,3-propanediamine dropwise to oleic acid (cis-octadecene-9-acid), reacting after the addition is completed, and purifying after the reaction is completed to obtain oleic acid amidopropyl-N,N-dimethyl tertiary amine; Step 2: dissolving oleamidopropyl-N,N-dimethyl tertiary amine in isopropanol-deionized water, adding a quaternizing agent, reacting, and purifying after the reaction to obtain oleamidopropyl-N,N-dimethyl quaternary ammonium salt; Step 3, dissolving γ-methacryloxypropyltrimethoxysilane (silane coupling agent KH-570) in an ethanol aqueous solution, adjusting the pH value to 4-5, adding graphene oxide-iron tetroxide composite material, and reacting after ultrasonic dispersion. After the reaction is completed, filtering, washing, and drying to obtain an olefin-modified graphene oxide-iron tetroxide composite material; immersing nylon 66 powder in an initiator solution, and performing a pre-initiation reaction under microwave radiation. After the reaction is completed, filtering to obtain pre-initiated nylon 66 powder; adding oleic acid amide propyl-N, N-dimethyl quaternary ammonium salt, olefin-modified graphene oxide-iron tetroxide composite material, and emulsifier to deionized water, after ultrasonic dispersion, adding pre-initiated nylon 66 powder, and performing a grafting reaction under microwave radiation. After the reaction is completed, filtering, washing, and drying to obtain an auxiliary agent; Step 4, blending and melting the additive and nylon 66 resin, spraying the melt through a spinneret to form fiber filaments, cooling with side air, drawing, and chopping to obtain heating nylon fiber; spinning the heating nylon fiber into yarn to obtain heating nylon yarn, spinning the heating nylon yarn into fabric to obtain nylon fabric; placing the nylon fabric in a finishing liquid for impregnation treatment, after the impregnation is completed, light curing treatment, washing, and drying to obtain modified nylon fabric; using the modified nylon fabric as the outer fabric and the inner fabric respectively, sewing the outer fabric and the inner fabric with equal areas, forming an air layer in the gap between the outer fabric and the inner fabric, and obtaining a magnetic therapy fabric containing heating nylon fiber.

[0006] Preferably, in the step 1, the molar ratio of oleic acid to N,N-dimethyl-1,3-propylenediamine is 1:(1.5-2.5), the dropping rate of N,N-dimethyl-1,3-propylenediamine is 1-2 mL / min, and the reaction conditions are closed reaction at 130-150° C. under nitrogen protection for 8-10 hours.

[0007] Preferably, in the step 2, the molar ratio of oleamidopropyl-N,N-dimethyl tertiary amine to the quaternizing agent is 1:(1.1-1.3), the amount of isopropanol-deionized water is 3-5 times the mass of oleamidopropyl-N,N-dimethyl tertiary amine, and the reaction conditions are 80-90° C. for 4-6 hours.

[0008] Preferably, the quaternizing agent comprises n-butyl bromide.

[0009] Preferably, the isopropanol-deionized water is a mixture of isopropanol and deionized water in a mass ratio of 1:2.

[0010] Preferably, in the step three, when preparing the alkenyl-modified graphene oxide-ferroferric oxide composite material, the mass ratio of the graphene oxide-ferroferric oxide composite material, γ-methacryloxypropyltrimethoxysilane, and ethanol aqueous solution is 0.2: (0.8-1.2): (60-100), and the reaction conditions are 50-70° C. for 6-8 hours.

[0011] Preferably, the ethanol aqueous solution comprises 75 wt % ethanol aqueous solution.

[0012] Preferably, the graphene oxide-ferroferric oxide composite material is prepared by the following steps: adding amino-modified nano-ferroferric oxide and nano-graphene oxide to deionized water, ultrasonically dispersing, adding 1-ethyl-(3-dimethylaminopropyl)carbodiimide, reacting, filtering, washing, and drying after the reaction to obtain the graphene oxide-ferroferric oxide composite material.

[0013] Preferably, the mass ratio of amino-modified nano-ferroferric oxide, nano-graphene oxide, deionized water, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide is (15-25):(75-85):(800-1200):(15-25), and the reaction conditions are stirring the reaction at a temperature of 75-85° C. for 20-30 hours.

[0014] Preferably, the amino-modified nano-iron tetroxide is prepared by the following steps: adding nano-iron tetroxide to an ethanol aqueous solution, ultrasonically dispersing, adding 3-aminopropyltrimethoxysilane (silane coupling agent KH-540), reacting, filtering, washing, and drying after the reaction to obtain the amino-modified nano-iron tetroxide.

[0015] Preferably, the mass ratio of nano-ferroferric oxide, 3-aminopropyltrimethoxysilane and ethanol aqueous solution is 0.1: (0.5-1.5): (50-70), and the reaction conditions are 40-50° C. for 6-10 hours.

[0016] Preferably, the ethanol aqueous solution comprises 75 wt % ethanol aqueous solution.

[0017] Preferably, in the step three, when preparing the pre-initiated nylon 66 powder, the mass ratio of nylon 66 powder to initiator solution is 1: (20-30), the microwave power is 350-450W, the temperature of the pre-initiation reaction is 60-80°C, and the time of the pre-initiation reaction is 20-40min; the initiator solution includes a potassium persulfate aqueous solution; and the mass percentage of potassium persulfate in the potassium persulfate aqueous solution is 0.2wt%-0.4wt%.

[0018] Preferably, in the step 3, when preparing the auxiliary agent, the mass ratio of oleamide propyl-N,N-dimethyl quaternary ammonium salt, olefin-modified graphene oxide-ferroferric oxide composite material, emulsifier, deionized water, and pre-initiated nylon 66 powder is (2-4): (4-8): (3-5): (600-800): 100, the microwave power is 350-450 W, the temperature of the grafting reaction is 60-80° C., and the time of the grafting reaction is 45-75 min; the emulsifier includes Span (sorbitan laurate).

[0019] Preferably, in step 4, the mass ratio of the auxiliary agent to the nylon 66 resin is (18-24):100, the melting temperature is 285-295°C, the pressure of the spinneret is 16-20MPa, the temperature of the side blowing air is 15-20°C, and the draft ratio is 1.3-1.5 times.

[0020] Preferably, in step 4, the yarn count of the heating nylon yarn is 20-30S (English count), and the gram weight of the nylon fabric is 200-220g / m 2 .

[0021] Preferably, in step 4, the mass ratio of nylon fabric to finishing liquid is 1:(15-25), the immersion treatment is carried out at room temperature, two immersions and two rollings, and the liquid carrying rate is 90%.

[0022] Preferably, the finishing liquid is prepared by the following steps: adding dimethyldiallylammonium chloride, acrylamide, hydroxyethyl methacrylate and a photoinitiator into deionized water, and ultrasonically dispersing to obtain the finishing liquid; wherein the mass ratio of dimethyldiallylammonium chloride, acrylamide, hydroxyethyl methacrylate, photoinitiator and deionized water is (16-20): (7-10): (13-18): (3.5-6): (300-500); the photoinitiator comprises phenyl (2,4,6-trimethylbenzoyl) lithium phosphate.

[0023] The present invention also provides a magnetic therapy fabric containing heat-generating nylon fibers, which is prepared by the method for preparing the magnetic therapy fabric containing heat-generating nylon fibers as described above.

[0024] An application of the magnetic therapy fabric containing the heat-generating nylon fiber as described above in textiles.

[0025] Compared with the prior art, the beneficial effects of the present invention are as follows: in the present invention, the magnetic therapy fabric containing heating nylon fiber includes an inner layer fabric and an outer layer fabric, and an air layer is formed by the gap between the two layers of fabric to improve the thermal insulation performance of the fabric. The fabric is made of nylon fiber and has good wear resistance. By adding an auxiliary agent, since the auxiliary agent includes a far-infrared heating material graphene oxide and a magnetic material ferroferric oxide, the far-infrared heating performance and magnetic therapy performance of the nylon fabric can be achieved; at the same time, the auxiliary agent also contains an alkyl quaternary ammonium salt, which can improve the antibacterial and antistatic properties of the nylon fabric; in addition, the nylon fabric is treated with finishing and modification, and the raw materials in the finishing liquid include dimethyldiallyl ammonium chloride, acrylamide, and hydroxyethyl methacrylate. Under the action of a photoinitiator, a film is polymerized on the surface of the nylon fabric and between the pores of the fabric under light conditions. The introduction of the quaternary ammonium salt dimethyldiallyl ammonium chloride can further improve the antibacterial and antistatic properties of the nylon fabric, and the introduction of acrylamide and hydroxyethyl methacrylate can improve the hydrophilicity of nylon, further improving the Hygroscopic performance; in the present invention, when preparing the auxiliary agent, oleic acid is used as the alkyl chain raw material, oleic acid and N, N-dimethyl-1, 3-propylenediamine undergo amidation reaction to obtain oleic acid amidopropyl-N, N-dimethyl tertiary amine, oleic acid amidopropyl-N, N-dimethyl tertiary amine reacts with a quaternizing agent to obtain oleic acid amidopropyl-N, N-dimethyl quaternary ammonium salt, and the graphene oxide-ferrous oxide composite material reacts with γ-methacryloxypropyltrimethoxysilane to obtain an olefin-modified graphene oxide-ferrous oxide composite material. The composite material is prepared by pre-initiating reaction of nylon 66 powder under the action of an initiator under microwave radiation conditions to induce active free radicals on the surface of nylon 66. The oleic acid amide propyl-N,N-dimethyl quaternary ammonium salt and olefin-modified graphene oxide-ferroferric oxide composite material react with the pre-initiated nylon 66 through the olefin groups on the molecules and are grafted onto the nylon 66 molecules, thereby improving the dispersion uniformity between the quaternary ammonium salt, graphene oxide-ferroferric oxide and nylon 66, and the far-infrared heating performance, magnetic therapy performance, antibacterial performance and antistatic performance are stable. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a process flow chart of the preparation of the auxiliary agent in the present invention; Figure 2 It is a bar graph showing the heat generation performance test results of the nylon fabrics prepared in Examples 1-4 of the present invention and Comparative Examples 1-2; Figure 3 The bar graph is a magnetic property test result of the nylon fabrics prepared in Examples 1-4 of the present invention and Comparative Examples 1-2; Figure 4 It is a bar graph showing the test results of the antibacterial properties of the nylon fabrics prepared in Examples 1-4 of the present invention and Comparative Examples 1-2; Figure 5It is a bar chart showing the test results of the antistatic properties of the nylon fabrics prepared in Examples 1-4 of the present invention and Comparative Examples 1-2. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0028] Example 1 This embodiment discloses a method for preparing a magnetic therapy fabric containing heat-generating nylon fibers, comprising the following steps: Step 1, under nitrogen protection, N,N-dimethyl-1,3-propylenediamine was added dropwise to oleic acid, the molar ratio of oleic acid to N,N-dimethyl-1,3-propylenediamine was 1:1.5, and the dropping speed of N,N-dimethyl-1,3-propylenediamine was 1mL / min. After the addition was completed, the reaction was closed at 130°C for 10 hours under nitrogen protection. After the reaction was completed, the unreacted N,N-dimethyl-1,3-propylenediamine and the generated water were removed by reduced pressure distillation at 80°C and 0.1MPa. Three times the mass of oleic acid was added to n-hexane for crystallization, and the filtered residue was washed with n-hexane for 3 times, and then vacuum dried at 60°C and 0.1MPa to constant weight to obtain oleic acid amide propyl-N,N-dimethyl tertiary amine; Step 2, dissolving oleamidopropyl-N,N-dimethyl tertiary amine in isopropanol-deionized water, adding n-butyl bromide, the molar ratio of oleamidopropyl-N,N-dimethyl tertiary amine to n-butyl bromide is 1:1.1, the amount of isopropanol-deionized water is 3 times the mass of oleamidopropyl-N,N-dimethyl tertiary amine, reacting at 80°C for 6 hours, after the reaction is completed, distilling under reduced pressure at 70°C and 0.1MPa to remove isopropanol and deionized water, adding 3 times the mass of oleamidopropyl-N,N-dimethyl tertiary amine n-hexane-ethyl acetate mixed solvent for crystallization, filtering, washing the filtered residue with n-hexane-ethyl acetate mixed solvent 3 times, and vacuum drying at 60°C and 0.1MPa to constant weight to obtain oleamidopropyl-N,N-dimethyl quaternary ammonium salt; wherein, isopropanol-deionized water is a mixture of isopropanol and deionized water in a mass ratio of 1:2; Step 3, dissolving γ-methacryloxypropyltrimethoxysilane in 75wt% ethanol aqueous solution, adjusting the pH value to 4.5 with acetic acid, adding graphene oxide-iron tetroxide composite material, the mass ratio of graphene oxide-iron tetroxide composite material, γ-methacryloxypropyltrimethoxysilane, and 75wt% ethanol aqueous solution is 0.2:1:80, ultrasonically dispersing at a frequency of 50kHz for 30min, reacting at a temperature of 60°C for 7h, filtering after the reaction, washing with ethanol 3 times, and drying in a 50°C vacuum drying oven for 24h to obtain an olefin-modified graphene oxide-iron tetroxide composite material; wherein the graphene oxide-iron tetroxide composite material comprises the following steps: adding amino-modified nano-iron tetroxide and nano-graphene oxide to deionized water, ultrasonically dispersing at a frequency of 50kHz for 30min, adding 1-ethyl-(3-dimethylaminopropyl)carbodiimide, amino-modified nano-iron tetroxide, nano-graphene oxide, deionized water, 1- The mass ratio of ethyl-(3-dimethylaminopropyl)carbodiimide is 20:80:1000:20, and the reaction is stirred at 80°C and 300r / min for 24 hours. After the reaction is completed, the mixture is filtered, washed with deionized water for 3 times, and dried in a 50°C vacuum drying oven for 24 hours to obtain a graphene oxide-ferroferric oxide composite material; wherein the amino-modified nano-ferroferric oxide is prepared by the following steps: adding nano-ferroferric oxide to a 75wt% ethanol aqueous solution, After ultrasonic dispersion at a frequency of 50kHz for 30 minutes, 3-aminopropyltrimethoxysilane was added. The mass ratio of nano-iron tetroxide, 3-aminopropyltrimethoxysilane and 75wt% ethanol aqueous solution was 0.1:1:60. The mixture was reacted at 45℃ for 8 hours. After the reaction, the mixture was filtered, washed with ethanol for 3 times, and dried in a vacuum drying oven at 50℃ for 24 hours to obtain amino-modified nano-iron tetroxide. Nylon 66 powder was immersed in a 0.2wt% potassium persulfate aqueous solution.The mass ratio of 2wt% potassium persulfate aqueous solution is 1:20, and a pre-initiation reaction is carried out under microwave radiation. After the reaction is completed, it is filtered to obtain pre-initiated nylon 66 powder; wherein the microwave power is 350W, the temperature of the pre-initiation reaction is 60°C, and the time of the pre-initiation reaction is 40min; oleamide propyl-N,N-dimethyl quaternary ammonium salt, olefin-modified graphene oxide-iron tetroxide composite material, and Span 20 are added to deionized water, and after ultrasonic dispersion at a frequency of 50kHz for 30min, the pre-initiated nylon 66 powder is added. The mass ratio of nylon 66 powder, oleamide propyl-N,N-dimethyl quaternary ammonium salt, olefin-modified graphene oxide-iron tetroxide composite material, Span 20, deionized water, and pre-initiated nylon 66 powder is 2:4:3:600:100, and the grafting reaction is carried out under microwave radiation. After the reaction is completed, it is filtered, washed with deionized water for 3 times, and placed in a vacuum drying oven at 50℃ for 24h to obtain an additive; wherein the microwave power is 350W, the grafting reaction temperature is 60℃, and the grafting reaction time is 75min;. Step 4: blend and melt the additive and nylon 66 resin, the mass ratio of the additive to nylon 66 resin is 18:100, the melting temperature is 285°C, the melt is ejected through the spinneret to form fiber filaments, the pressure of the spinneret is 18MPa, side blowing cooling, the temperature of the side blowing is 18°C, stretching, the stretching multiple is 1.4 times, short cutting, and heating nylon fiber is obtained, the length of the heating nylon fiber is 38mm; the heating nylon fiber is spun into yarn to obtain heating nylon yarn, the yarn count of the heating nylon yarn is 25S, the heating nylon yarn is spun into fabric through a knitting process, and nylon fabric is obtained, and the gram weight of the nylon fabric is 210g / m 2 ; The nylon fabric is placed in the finishing liquid for immersion treatment, the mass ratio of the nylon fabric to the finishing liquid is 1:15, the immersion treatment is carried out at room temperature, two immersions and two rollings, the liquid carrying rate is 90%, after the immersion is completed, both sides of the nylon fabric after the immersion treatment are irradiated under a blue light with a wavelength of 405nm for 30min for curing reaction, washed with deionized water 3 times, and dried at 50°C to obtain a modified nylon fabric; wherein the finishing liquid is prepared by the following steps: dimethyldiallylammonium chloride, acrylamide, hydroxyethyl methacrylate, phenyl (2,4,6-trimethyl The invention discloses a magnetic therapy fabric containing heating nylon fiber, wherein the mass ratio of dimethyldiallylammonium chloride, acrylamide, hydroxyethyl methacrylate, phenyl (2,4,6-trimethylbenzoyl) lithium phosphate and deionized water is 18:8:15:5:400. The outer and inner fabrics are respectively made of modified nylon fabrics, and the outer and inner fabrics are sewn with equal areas by polyester sewing thread. An air layer is formed in the gap between the outer and inner fabrics, so as to obtain a magnetic therapy fabric containing heating nylon fiber.

[0029] Example 2 This embodiment discloses a method for preparing a magnetic therapy fabric containing heat-generating nylon fibers, comprising the following steps: Step 1, under nitrogen protection, N,N-dimethyl-1,3-propylenediamine was added dropwise to oleic acid, the molar ratio of oleic acid to N,N-dimethyl-1,3-propylenediamine was 1:2.5, and the dropping speed of N,N-dimethyl-1,3-propylenediamine was 2mL / min. After the addition was completed, the reaction was closed at 150°C for 8h under nitrogen protection. After the reaction was completed, the unreacted N,N-dimethyl-1,3-propylenediamine and the generated water were removed by reduced pressure distillation at 80°C and 0.1MPa. Three times the mass of oleic acid was added to n-hexane for crystallization, and the filtered residue was washed with n-hexane for 3 times, and then vacuum dried at 60°C and 0.1MPa to constant weight to obtain oleic acid amide propyl-N,N-dimethyl tertiary amine; Step 2, dissolving oleamidopropyl-N,N-dimethyl tertiary amine in isopropanol-deionized water, adding n-butyl bromide, the molar ratio of oleamidopropyl-N,N-dimethyl tertiary amine to n-butyl bromide is 1:1.3, the amount of isopropanol-deionized water is 5 times the mass of oleamidopropyl-N,N-dimethyl tertiary amine, reacting at 90°C for 4 hours, after the reaction is completed, distilling under reduced pressure at 70°C and 0.1MPa to remove isopropanol and deionized water, adding 3 times the mass of oleamidopropyl-N,N-dimethyl tertiary amine n-hexane-ethyl acetate mixed solvent for crystallization, filtering, washing the filtered residue with n-hexane-ethyl acetate mixed solvent 3 times, and vacuum drying at 60°C and 0.1MPa to constant weight to obtain oleamidopropyl-N,N-dimethyl quaternary ammonium salt; wherein, isopropanol-deionized water is a mixture of isopropanol and deionized water in a mass ratio of 1:2; Step 3, prepare an olefin-modified graphene oxide-iron tetroxide composite material; the preparation method of the olefin-modified graphene oxide-iron tetroxide composite material is the same as that of Example 1; immerse nylon 66 powder in a 0.4wt% potassium persulfate aqueous solution, the mass ratio of nylon 66 powder to 0.4wt% potassium persulfate aqueous solution is 1:30, and a pre-initiation reaction is carried out under microwave radiation conditions. After the reaction is completed, filter to obtain pre-initiated nylon 66 powder; wherein the microwave power is 450W, the pre-initiation reaction temperature is 80°C, and the pre-initiation reaction time is 20min; oleic acid amide propyl-N, N-dimethyl quaternary ammonium salt, olefin-modified graphene oxide-iron tetroxide The composite material and Span 20 are added into deionized water, and after ultrasonic dispersion at a frequency of 50kHz for 30 minutes, the pre-initiated nylon 66 powder, oleamide propyl-N, N-dimethyl quaternary ammonium salt, olefin-modified graphene oxide-ferrosoferric oxide composite material, Span 20, deionized water, and pre-initiated nylon 66 powder are added in a mass ratio of 4:8:5:800:100, and a grafting reaction is carried out under microwave radiation. After the reaction is completed, the mixture is filtered, washed with deionized water for 3 times, and dried in a vacuum drying oven at 50°C for 24 hours to obtain an additive; wherein the microwave power is 450W, the grafting reaction temperature is 80°C, and the grafting reaction time is 45 minutes; Step 4: blend and melt the additive and nylon 66 resin, the mass ratio of the additive to nylon 66 resin is 24:100, the melting temperature is 295°C, the melt is ejected through the spinneret to form fiber filaments, the pressure of the spinneret is 18MPa, the side blowing is cooled, the temperature of the side blowing is 18°C, stretching, the stretching multiple is 1.4 times, and short-cutting to obtain heating nylon fiber, the length of the heating nylon fiber is 38mm; the heating nylon fiber is spun into yarn to obtain heating nylon yarn, the yarn count of the heating nylon yarn is 25S, and the heating nylon yarn is spun into fabric through a knitting process to obtain nylon fabric, and the gram weight of the nylon fabric is 210g / m 2 ; The nylon fabric is placed in a finishing liquid for immersion treatment, the mass ratio of the nylon fabric to the finishing liquid is 1:25, the immersion treatment is carried out at room temperature, two immersions and two rollings, the liquid carrying rate is 90%, after the immersion is completed, both sides of the nylon fabric after the immersion treatment are irradiated under blue light with a wavelength of 405nm for 30 minutes for curing reaction, washed with deionized water 3 times, and dried at 50°C to obtain a modified nylon fabric; wherein the preparation method of the finishing liquid is the same as that of Example 1; the modified nylon fabric is used as the outer fabric and the inner fabric respectively, and the outer fabric and the inner fabric are sewn with equal areas using polyester sewing thread, and the gap between the outer fabric and the inner fabric forms an air layer to obtain a magnetic therapy fabric containing heating nylon fiber.

[0030] Example 3 This embodiment discloses a method for preparing a magnetic therapy fabric containing heat-generating nylon fibers, comprising the following steps: Step 1, under nitrogen protection, N,N-dimethyl-1,3-propylenediamine was added dropwise to oleic acid, the molar ratio of oleic acid to N,N-dimethyl-1,3-propylenediamine was 1:1.8, and the dropping speed of N,N-dimethyl-1,3-propylenediamine was 1.5mL / min. After the addition was completed, the reaction was closed at 140°C for 9h under nitrogen protection. After the reaction was completed, the unreacted N,N-dimethyl-1,3-propylenediamine and the generated water were removed by reduced pressure distillation at 80°C and 0.1MPa. Three times the mass of oleic acid was added to n-hexane for crystallization, and the filtered residue was washed with n-hexane for 3 times, and then vacuum dried at 60°C and 0.1MPa to constant weight to obtain oleic acid amide propyl-N,N-dimethyl tertiary amine; Step 2, dissolving oleamidopropyl-N,N-dimethyl tertiary amine in isopropanol-deionized water, adding n-butyl bromide, the molar ratio of oleamidopropyl-N,N-dimethyl tertiary amine to n-butyl bromide is 1:1.15, the amount of isopropanol-deionized water is 4 times the mass of oleamidopropyl-N,N-dimethyl tertiary amine, reacting at 85°C for 5 hours, after the reaction is completed, distilling under reduced pressure at 70°C and 0.1MPa to remove isopropanol and deionized water, adding 3 times the mass of oleamidopropyl-N,N-dimethyl tertiary amine n-hexane-ethyl acetate mixed solvent for crystallization, filtering, washing the filtered residue with n-hexane-ethyl acetate mixed solvent 3 times, and vacuum drying at 60°C and 0.1MPa to constant weight to obtain oleamidopropyl-N,N-dimethyl quaternary ammonium salt; wherein, isopropanol-deionized water is a mixture of isopropanol and deionized water in a mass ratio of 1:2; Step 3, prepare an olefin-modified graphene oxide-iron tetroxide composite material; the preparation method of the olefin-modified graphene oxide-iron tetroxide composite material is the same as that of Example 1; immerse nylon 66 powder in a 0.3wt% potassium persulfate aqueous solution, the mass ratio of nylon 66 powder to 0.3wt% potassium persulfate aqueous solution is 1:25, and a pre-initiation reaction is carried out under microwave radiation conditions. After the reaction is completed, filter to obtain pre-initiated nylon 66 powder; wherein the microwave power is 400W, the pre-initiation reaction temperature is 70°C, and the pre-initiation reaction time is 30min; oleic acid amide propyl-N, N-dimethyl quaternary ammonium salt, olefin-modified graphene oxide-iron tetroxide composite The material and Span 20 are added into deionized water, and after ultrasonic dispersion at a frequency of 50kHz for 30 minutes, the pre-initiated nylon 66 powder, oleamide propyl-N, N-dimethyl quaternary ammonium salt, olefin-modified graphene oxide-ferroferric oxide composite material, Span 20, deionized water, and pre-initiated nylon 66 powder are added in a mass ratio of 2.5:5:3.5:650:100, and a grafting reaction is carried out under microwave radiation. After the reaction is completed, the mixture is filtered, washed with deionized water for 3 times, and dried in a vacuum drying oven at 50°C for 24 hours to obtain an auxiliary agent; wherein the microwave power is 400W, the grafting reaction temperature is 70°C, and the grafting reaction time is 60 minutes; Step 4: blend and melt the additive and nylon 66 resin, the mass ratio of the additive to nylon 66 resin is 20:100, the melting temperature is 290°C, the melt is ejected through the spinneret to form fiber filaments, the pressure of the spinneret is 18MPa, side blowing cooling, the temperature of the side blowing is 18°C, stretching, the stretching multiple is 1.4 times, short cutting, and heating nylon fiber is obtained, the length of the heating nylon fiber is 38mm; the heating nylon fiber is spun into yarn to obtain heating nylon yarn, the yarn count of the heating nylon yarn is 25S, the heating nylon yarn is spun into fabric through a knitting process, and nylon fabric is obtained, and the gram weight of the nylon fabric is 210g / m 2 ; The nylon fabric is placed in a finishing liquid for immersion treatment, the mass ratio of the nylon fabric to the finishing liquid is 1:25, the immersion treatment is carried out at room temperature, two immersions and two rollings, the liquid carrying rate is 90%, after the immersion is completed, both sides of the nylon fabric after the immersion treatment are irradiated under blue light with a wavelength of 405nm for 30 minutes for curing reaction, washed with deionized water 3 times, and dried at 50°C to obtain a modified nylon fabric; wherein the preparation method of the finishing liquid is the same as that of Example 1; the modified nylon fabric is used as the outer fabric and the inner fabric respectively, and the outer fabric and the inner fabric are sewn with equal areas using polyester sewing thread, and the gap between the outer fabric and the inner fabric forms an air layer to obtain a magnetic therapy fabric containing heating nylon fiber.

[0031] Example 4 This embodiment discloses a method for preparing a magnetic therapy fabric containing heat-generating nylon fibers, comprising the following steps: Step 1, under nitrogen protection, N,N-dimethyl-1,3-propylenediamine was added dropwise to oleic acid, the molar ratio of oleic acid to N,N-dimethyl-1,3-propylenediamine was 1:2.2, and the dropping speed of N,N-dimethyl-1,3-propylenediamine was 1.5mL / min. After the addition was completed, the reaction was closed at 140°C for 9h under nitrogen protection. After the reaction was completed, the unreacted N,N-dimethyl-1,3-propylenediamine and the generated water were removed by reduced pressure distillation at 80°C and 0.1MPa. Three times the mass of oleic acid was added to n-hexane for crystallization, and the filtered residue was washed with n-hexane for 3 times, and then vacuum dried at 60°C and 0.1MPa to constant weight to obtain oleic acid amide propyl-N,N-dimethyl tertiary amine; Step 2, dissolving oleamidopropyl-N,N-dimethyl tertiary amine in isopropanol-deionized water, adding n-butyl bromide, the molar ratio of oleamidopropyl-N,N-dimethyl tertiary amine to n-butyl bromide is 1:1.25, the amount of isopropanol-deionized water is 4 times the mass of oleamidopropyl-N,N-dimethyl tertiary amine, reacting at 85°C for 5 hours, after the reaction is completed, performing reduced pressure distillation at 70°C and 0.1MPa to remove isopropanol and deionized water, adding a n-hexane-ethyl acetate mixed solvent of 3 times the mass of oleamidopropyl-N,N-dimethyl tertiary amine for crystallization, filtering, washing the filtered residue with a n-hexane-ethyl acetate mixed solvent for 3 times, and vacuum drying at 60°C and 0.1MPa to constant weight to obtain oleamidopropyl-N,N-dimethyl quaternary ammonium salt; wherein the isopropanol-deionized water is a mixture of isopropanol and deionized water in a mass ratio of 1:2; Step 3, prepare an olefin-modified graphene oxide-iron tetroxide composite material; the preparation method of the olefin-modified graphene oxide-iron tetroxide composite material is the same as that of Example 1; immerse nylon 66 powder in a 0.3wt% potassium persulfate aqueous solution, the mass ratio of nylon 66 powder to 0.3wt% potassium persulfate aqueous solution is 1:25, and a pre-initiation reaction is carried out under microwave radiation conditions. After the reaction is completed, filter to obtain pre-initiated nylon 66 powder; wherein the microwave power is 400W, the pre-initiation reaction temperature is 70°C, and the pre-initiation reaction time is 30min; oleic acid amide propyl-N, N-dimethyl quaternary ammonium salt, olefin-modified graphene oxide-iron tetroxide composite The material and Span 20 are added into deionized water, and after ultrasonic dispersion at a frequency of 50kHz for 30 minutes, the pre-initiated nylon 66 powder, oleamide propyl-N, N-dimethyl quaternary ammonium salt, olefin-modified graphene oxide-ferroferric oxide composite material, Span 20, deionized water, and pre-initiated nylon 66 powder are added in a mass ratio of 3.5:7:4.5:750:100, and a grafting reaction is carried out under microwave radiation. After the reaction is completed, the mixture is filtered, washed with deionized water for 3 times, and dried in a vacuum drying oven at 50°C for 24 hours to obtain an auxiliary agent; wherein the microwave power is 400W, the grafting reaction temperature is 70°C, and the grafting reaction time is 60 minutes; Step 4: blend and melt the additive and nylon 66 resin, the mass ratio of the additive to nylon 66 resin is 22:100, the melting temperature is 290°C, the melt is ejected through the spinneret to form fiber filaments, the pressure of the spinneret is 18MPa, side blowing cooling, the temperature of the side blowing is 18°C, stretching, the stretching multiple is 1.4 times, short cutting, and heating nylon fiber is obtained, the length of the heating nylon fiber is 38mm; the heating nylon fiber is spun into yarn to obtain heating nylon yarn, the yarn count of the heating nylon yarn is 25S, the heating nylon yarn is spun into fabric through a knitting process, and nylon fabric is obtained, and the gram weight of the nylon fabric is 210g / m 2 ; The nylon fabric is placed in a finishing liquid for immersion treatment, the mass ratio of the nylon fabric to the finishing liquid is 1:25, the immersion treatment is carried out at room temperature, two immersions and two rollings, the liquid carrying rate is 90%, after the immersion is completed, both sides of the nylon fabric after the immersion treatment are irradiated under blue light with a wavelength of 405nm for 30 minutes for curing reaction, washed with deionized water 3 times, and dried at 50°C to obtain a modified nylon fabric; wherein the preparation method of the finishing liquid is the same as that of Example 1; the modified nylon fabric is used as the outer fabric and the inner fabric respectively, and the outer fabric and the inner fabric are sewn with equal areas using polyester sewing thread, and the gap between the outer fabric and the inner fabric forms an air layer to obtain a magnetic therapy fabric containing heating nylon fiber.

[0032] Comparative Example 1 This comparative example discloses a method for preparing a magnetic therapy fabric containing heat-generating nylon fibers, comprising the following steps: Step 1, prepare an olefin-modified graphene oxide-iron tetroxide composite material; the preparation method of the olefin-modified graphene oxide-iron tetroxide composite material is the same as that of Example 1; immerse nylon 66 powder in a 0.2wt% potassium persulfate aqueous solution, the mass ratio of nylon 66 powder to 0.2wt% potassium persulfate aqueous solution is 1:20, and a pre-initiation reaction is carried out under microwave radiation conditions. After the reaction is completed, filter to obtain pre-initiated nylon 66 powder; wherein the microwave power is 350W, the pre-initiation reaction temperature is 60°C, and the pre-initiation reaction time is 40min; olefin-modified graphene oxide-iron tetroxide composite material is prepared; The iron composite material and Span 20 were added to deionized water, and after ultrasonic dispersion at a frequency of 50kHz for 30 minutes, pre-initiated nylon 66 powder was added, and the mass ratio of olefin-modified graphene oxide-iron tetroxide composite material, Span 20, deionized water, and pre-initiated nylon 66 powder was 4:3:600:102. The grafting reaction was carried out under microwave radiation. After the reaction was completed, it was filtered, washed with deionized water for 3 times, and placed in a vacuum drying oven at 50°C for 24 hours to obtain an auxiliary agent; wherein the microwave power was 350W, the grafting reaction temperature was 60°C, and the grafting reaction time was 75 minutes; Step 2: blend and melt the additive and nylon 66 resin, the mass ratio of the additive to the nylon 66 resin is 18:100, the melting temperature is 285°C, the melt is ejected through the spinneret to form fiber filaments, the pressure of the spinneret is 18MPa, the side blowing is cooled, the temperature of the side blowing is 18°C, stretching, the stretching multiple is 1.4 times, and short-cutting to obtain heating nylon fiber, the length of the heating nylon fiber is 38mm; the heating nylon fiber is spun into yarn to obtain heating nylon yarn, the yarn count of the heating nylon yarn is 25S, the heating nylon yarn is spun into fabric through a knitting process to obtain nylon fabric, the gram weight of the nylon fabric is 210g / m 2 ; The nylon fabric is placed in a finishing liquid for immersion treatment, the mass ratio of the nylon fabric to the finishing liquid is 1:15, the immersion treatment is carried out at room temperature, two immersions and two rollings, the liquid carrying rate is 90%, after the immersion is completed, both sides of the nylon fabric after the immersion treatment are irradiated under blue light with a wavelength of 405nm for 30 minutes for curing reaction, washed with deionized water 3 times, and dried at 50°C to obtain a modified nylon fabric; wherein the preparation method of the finishing liquid is the same as that of Example 1; the modified nylon fabric is used as the outer fabric and the inner fabric respectively, and the outer fabric and the inner fabric are sewn with equal areas using polyester sewing thread, and the gap between the outer fabric and the inner fabric forms an air layer to obtain a magnetic therapy fabric containing heating nylon fiber.

[0033] Comparative Example 2 This comparative example discloses a method for preparing a magnetic therapy fabric containing heat-generating nylon fibers, comprising the following steps: Step 1, under nitrogen protection, N,N-dimethyl-1,3-propylenediamine was added dropwise to oleic acid, the molar ratio of oleic acid to N,N-dimethyl-1,3-propylenediamine was 1:1.5, and the dropping speed of N,N-dimethyl-1,3-propylenediamine was 1mL / min. After the addition was completed, the reaction was closed at 130°C for 10 hours under nitrogen protection. After the reaction was completed, the unreacted N,N-dimethyl-1,3-propylenediamine and the generated water were removed by reduced pressure distillation at 80°C and 0.1MPa. Three times the mass of oleic acid was added to n-hexane for crystallization, and the filtered residue was washed with n-hexane for 3 times, and then vacuum dried at 60°C and 0.1MPa to constant weight to obtain oleic acid amide propyl-N,N-dimethyl tertiary amine; Step 2, dissolving oleamidopropyl-N,N-dimethyl tertiary amine in isopropanol-deionized water, adding n-butyl bromide, the molar ratio of oleamidopropyl-N,N-dimethyl tertiary amine to n-butyl bromide is 1:1.1, the amount of isopropanol-deionized water is 3 times the mass of oleamidopropyl-N,N-dimethyl tertiary amine, reacting at 80°C for 6 hours, after the reaction is completed, distilling under reduced pressure at 70°C and 0.1MPa to remove isopropanol and deionized water, adding 3 times the mass of oleamidopropyl-N,N-dimethyl tertiary amine n-hexane-ethyl acetate mixed solvent for crystallization, filtering, washing the filtered residue with n-hexane-ethyl acetate mixed solvent 3 times, and vacuum drying at 60°C and 0.1MPa to constant weight to obtain oleamidopropyl-N,N-dimethyl quaternary ammonium salt; wherein, isopropanol-deionized water is a mixture of isopropanol and deionized water in a mass ratio of 1:2; Step 3: immerse nylon 66 powder in a 0.2wt% potassium persulfate aqueous solution, wherein the mass ratio of nylon 66 powder to the 0.2wt% potassium persulfate aqueous solution is 1:20, and a pre-initiation reaction is carried out under microwave radiation. After the reaction is completed, the pre-initiation nylon 66 powder is filtered to obtain the pre-initiation nylon 66 powder; wherein the microwave power is 350W, the pre-initiation reaction temperature is 60°C, and the pre-initiation reaction time is 40min; oleamide propyl-N,N-dimethyl quaternary ammonium salt and Span 20 are added to deionized water, and the reaction is carried out at a frequency of 50kHz. After ultrasonic dispersion for 30 minutes, the pre-initiated nylon 66 powder, oleic acid amide propyl-N, N-dimethyl quaternary ammonium salt, Span 20, deionized water, and pre-initiated nylon 66 powder were added in a mass ratio of 2:3:600:100, and the grafting reaction was carried out under microwave radiation. After the reaction was completed, it was filtered, washed with deionized water for 3 times, and placed in a vacuum drying oven at 50°C for 24 hours to obtain an auxiliary agent; wherein, the microwave power was 350W, the grafting reaction temperature was 60°C, and the grafting reaction time was 75 minutes; Step 4: blend and melt the auxiliary agent, graphene oxide-ferroferric oxide composite material and nylon 66 resin, the mass ratio of the auxiliary agent, graphene oxide-ferroferric oxide composite material and nylon 66 resin is 17.2:0.8:100, the melting temperature is 285°C, the melt is ejected through a spinneret to form fiber filaments, the pressure of the spinneret is 18MPa, the side blowing is cooled, the temperature of the side blowing is 18°C, the drawing is 1.4 times, and the short cutting is performed to obtain a heating nylon fiber, the length of the heating nylon fiber is 38mm; the heating nylon fiber is spun into yarn to obtain a heating nylon yarn, the yarn count of the heating nylon yarn is 25S, and the heating nylon yarn is spun into fabric through a knitting process to obtain a nylon fabric, and the gram weight of the nylon fabric is 210g / m 2 ; The nylon fabric is placed in a finishing liquid for immersion treatment, the mass ratio of the nylon fabric to the finishing liquid is 1:15, the immersion treatment is carried out at room temperature, two immersions and two rollings, the liquid carrying rate is 90%, after the immersion is completed, both sides of the nylon fabric after the immersion treatment are irradiated under blue light with a wavelength of 405nm for 30 minutes for curing reaction, washed with deionized water 3 times, and dried at 50°C to obtain a modified nylon fabric; wherein the preparation method of the finishing liquid is the same as that of Example 1; the modified nylon fabric is used as the outer fabric and the inner fabric respectively, and the outer fabric and the inner fabric are sewn with equal areas using polyester sewing thread, and the gap between the outer fabric and the inner fabric forms an air layer to obtain a magnetic therapy fabric containing heating nylon fiber.

[0034] In the above embodiments and comparative examples, oleic acid (cis-octadecene-9-acid) was purchased from Guangzhou Xiangmei Chemical Technology Co., Ltd., CAS No.: 112-80-1, content: 99%; nano-graphene oxide is graphene oxide nanosheets, purchased from Shanghai Naio Nano Technology Co., Ltd., item No.: NO-C-068-1, thickness: <2nm, diameter: <20um; nano-iron tetroxide was purchased from Wenzhou Jingcheng Chemical Co., Ltd., model: SS-F908M, average particle size: 30-50nm; nylon 66 powder was purchased from Dongguan Chengjie Plastic Raw Materials Co., Ltd., brand: DuPont, grade: 101L, particle size: 150 mesh; nylon 66 resin was purchased from Dongguan Heyue Plastic Chemical Co., Ltd., product name: polyamide 66, specification model: 101L, product state: granular; acrylic fiber is chopped acrylic filament, the length of acrylic fiber is 38mm, acrylic filament was purchased from Shaoxing Xineng Textile Technology Co., Ltd., item number: JL-1, thickness: 150D; polyester sewing thread was purchased from Guangzhou Hongqiao Industrial Co., Ltd., specification: 120D / 3-80#.

[0035] Test Case (1) Heating performance: The temperature rise value (°C) of the nylon fabric (outer fabric) samples prepared in Examples 1-4 and Comparative Examples 1-2 after 30s of far-infrared irradiation was measured with reference to the "Far-infrared irradiation temperature rise test" in the standard GB / T30127-2013 "Testing and evaluation of far-infrared performance of textiles". Each sample was tested three times, and the average value of the three temperature rises of each sample was taken as the measurement result. The measurement results are shown in Table 1:

[0036] As can be seen from Table 1, the nylon fabric prepared by the present invention has good far-infrared heating performance due to the addition of far-infrared heating material graphene oxide. Compared with Example 1, in Comparative Example 2, the graphene oxide-ferroferric oxide composite material is not connected to the nylon 66 molecule through a stable chemical bond to prepare the auxiliary agent, resulting in a decrease in its dispersion uniformity in the nylon 66 resin and a decrease in far-infrared heating performance.

[0037] (2) Magnetic properties: The magnetic induction intensity of the nylon fabric (outer fabric) samples prepared in Examples 1-4 and Comparative Examples 1-2 was measured with reference to Standard FZ / T01116-2012 "Detection and Evaluation of Magnetic Properties of Textiles". The measurement results are shown in Table 2:

[0038] As can be seen from Table 2, the nylon fabric prepared by the present invention has good magnetic properties due to the addition of the magnetic material ferroferric oxide. Compared with Example 1, in Comparative Example 2, the graphene oxide-ferroferric oxide composite material is not connected to the nylon 66 molecule through a stable chemical bond to prepare the auxiliary agent, resulting in a decrease in its dispersion uniformity in the nylon 66 resin and a decrease in magnetic properties.

[0039] Antibacterial performance: The antibacterial rate of the nylon fabric (outer fabric) samples prepared in Examples 1-4 and Comparative Examples 1-2 after washing 50 times was measured with reference to the standard FZ / T73023-2006 "Antibacterial Knitwear". The results are shown in Table 3:

[0040] As shown in Table 3, the nylon fabric prepared by the present invention has good antibacterial properties due to the introduction of graphene oxide and quaternary ammonium salt. Compared with Example 1, in Comparative Example 1, the antibacterial property is reduced due to the absence of the addition of quaternary ammonium salt; in Comparative Example 2, the graphene oxide-ferroferric oxide composite material is not connected to the nylon 66 molecule through a stable chemical bond to prepare an auxiliary agent, resulting in a decrease in its dispersion uniformity in the nylon 66 resin and a decrease in antibacterial properties.

[0041] (4) Antistatic performance: The antistatic performance of the nylon fabric (outer fabric) samples prepared in Examples 1-4 and Comparative Examples 1-2 was measured with reference to the standard GB / T12703.2-2009 "Evaluation of electrostatic properties of textiles Part 2: Charge surface density". The results of the charge surface density measurement are shown in Table 4:

[0042] As shown in Table 4, the nylon fabric prepared by the present invention has good antistatic properties due to the introduction of graphene oxide and quaternary ammonium salt. Compared with Example 1, in Comparative Example 1, the antistatic property is reduced due to the absence of the addition of quaternary ammonium salt; in Comparative Example 2, the graphene oxide-ferroferric oxide composite material is not connected to the nylon 66 molecule through a stable chemical bond to prepare an auxiliary agent, resulting in a decrease in its dispersion uniformity in the nylon 66 resin and a decrease in antistatic property.

[0043] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a magnetic therapy fabric containing heating nylon fiber, characterized in that: The following steps are involved: Step 1, adding N,N-dimethyl-1,3-propylenediamine dropwise to oleic acid, reacting after the addition is completed, and purifying after the reaction is completed to obtain oleic acid amidopropyl-N,N-dimethyl tertiary amine; Step 2: dissolving oleamidopropyl-N,N-dimethyl tertiary amine in isopropanol-deionized water, adding a quaternizing agent, reacting, and purifying after the reaction to obtain oleamidopropyl-N,N-dimethyl quaternary ammonium salt; Step 3, dissolving γ-methacryloxypropyltrimethoxysilane in an ethanol aqueous solution, adjusting the pH value to 4-5, adding the graphene oxide-ferroferric oxide composite material, and reacting after ultrasonic dispersion. After the reaction is completed, filtering, washing, and drying to obtain an olefin-modified graphene oxide-ferroferric oxide composite material; The nylon 66 powder is immersed in an initiator solution, and a pre-initiation reaction is carried out under microwave radiation conditions. After the reaction is completed, the pre-initiated nylon 66 powder is filtered to obtain the pre-initiated nylon 66 powder; oleamide propyl-N,N-dimethyl quaternary ammonium salt, olefin-modified graphene oxide-ferroferric oxide composite material, and an emulsifier are added to deionized water, and after ultrasonic dispersion, the pre-initiated nylon 66 powder is added, and a grafting reaction is carried out under microwave radiation conditions. After the reaction is completed, the solution is filtered, washed, and dried to obtain an auxiliary agent; Step 4, blending and melting the additive and nylon 66 resin, spraying the melt through a spinneret to form fiber filaments, cooling with side air, drawing, and chopping to obtain heating nylon fiber; spinning the heating nylon fiber into yarn to obtain heating nylon yarn, spinning the heating nylon yarn into fabric to obtain nylon fabric; placing the nylon fabric in a finishing liquid for impregnation treatment, after the impregnation is completed, light curing treatment, washing, and drying to obtain modified nylon fabric; using the modified nylon fabric as the outer fabric and the inner fabric respectively, sewing the outer fabric and the inner fabric with equal areas, forming an air layer in the gap between the outer fabric and the inner fabric, and obtaining a magnetic therapy fabric containing heating nylon fiber.

2. The method for preparing a magnetic therapy fabric containing heat-generating nylon fiber according to claim 1, characterized in that: In the step 1, the molar ratio of oleic acid to N,N-dimethyl-1,3-propylenediamine is 1:(1.5-2.5), the dropping speed of N,N-dimethyl-1,3-propylenediamine is 1-2 mL / min, and the reaction conditions are a closed reaction at 130-150° C. under nitrogen protection for 8-10 hours.

3. The method for preparing a magnetic therapy fabric containing heat-generating nylon fiber according to claim 1, characterized in that: In the step 2, the molar ratio of oleamidopropyl-N,N-dimethyl tertiary amine to the quaternizing agent is 1:(1.1-1.3), the amount of isopropanol-deionized water is 3-5 times the mass of oleamidopropyl-N,N-dimethyl tertiary amine, and the reaction conditions are 4-6 hours at a temperature of 80-90°C; the quaternizing agent includes n-butyl bromide; the isopropanol-deionized water is a mixture of isopropanol and deionized water in a mass ratio of 1:

2.

4. The method for preparing a magnetic therapy fabric containing heat-generating nylon fiber according to claim 1, characterized in that: In the step three, when preparing the alkenyl-modified graphene oxide-ferroferric oxide composite material, the mass ratio of the graphene oxide-ferroferric oxide composite material, γ-methacryloxypropyltrimethoxysilane, and ethanol aqueous solution is 0.2: (0.8-1.2): (60-100), and the reaction conditions are to react at a temperature of 50-70°C for 6-8h; wherein the graphene oxide-ferroferric oxide composite material comprises the following steps of preparing: adding amino-modified nano-ferroferric oxide and nano-graphene oxide to deionized water, ultrasonically dispersing, adding 1-ethyl-(3-dimethylaminopropyl)carbodiimide, reacting, filtering, washing, and drying after the reaction to obtain the graphene oxide-ferroferric oxide composite material; the amino-modified nano-ferroferric oxide, nano-graphene oxide, The mass ratio of deionized water and 1-ethyl-(3-dimethylaminopropyl)carbodiimide is (15-25):(75-85):(800-1200):(15-25), and the reaction condition is to stir and react at a temperature of 75-85°C for 20-30 hours; wherein the amino-modified nano-iron tetroxide comprises the following steps: adding nano-iron tetroxide to an ethanol aqueous solution, ultrasonically dispersing, adding 3-aminopropyltrimethoxysilane, reacting, filtering, washing, and drying after the reaction to obtain the amino-modified nano-iron tetroxide; the mass ratio of nano-iron tetroxide, 3-aminopropyltrimethoxysilane, and ethanol aqueous solution is 0.1:(0.5-1.5):(50-70), and the reaction condition is to react at a temperature of 40-50°C for 6-10 hours.

5. The method for preparing a magnetic therapy fabric containing heat-generating nylon fiber according to claim 1, characterized in that: In the step three, when preparing the pre-initiated nylon 66 powder, the mass ratio of nylon 66 powder to initiator solution is 1: (20-30), the microwave power is 350-450W, the temperature of the pre-initiation reaction is 60-80°C, and the time of the pre-initiation reaction is 20-40min; the initiator solution includes a potassium persulfate aqueous solution; the mass percentage of potassium persulfate in the potassium persulfate aqueous solution is 0.2wt%-0.4wt%.

6. The method for preparing a magnetic therapy fabric containing heat-generating nylon fiber according to claim 1, characterized in that: In the step 3, when preparing the auxiliary agent, the mass ratio of oleamide propyl-N,N-dimethyl quaternary ammonium salt, olefin-modified graphene oxide-ferroferric oxide composite material, emulsifier, deionized water, and pre-initiated nylon 66 powder is (2-4): (4-8): (3-5): (600-800): 100, the microwave power is 350-450 W, the temperature of the grafting reaction is 60-80° C., and the time of the grafting reaction is 45-75 min.

7. The method for preparing a magnetic therapy fabric containing heat-generating nylon fiber according to claim 1, characterized in that: In the step 4, the mass ratio of the auxiliary agent to the nylon 66 resin is (18-24): 100, the melting temperature is 285-295°C, the pressure of the spinneret is 16-20MPa, the temperature of the side blowing is 15-20°C, and the drafting multiple is 1.3-1.5 times; the yarn count of the heating nylon yarn is 20-30S, and the gram weight of the nylon fabric is 200-220g / m 2 .

8. The method for preparing a magnetic therapy fabric containing heat-generating nylon fiber according to claim 1, characterized in that: In the step 4, the mass ratio of nylon fabric to finishing liquid is 1: (15-25), the immersion treatment is carried out at room temperature, two immersions and two rollings, and the liquid carrying rate is 90%; the finishing liquid is prepared by the following steps: adding dimethyldiallylammonium chloride, acrylamide, hydroxyethyl methacrylate, and a photoinitiator into deionized water, and ultrasonically dispersing to obtain a finishing liquid; wherein the mass ratio of dimethyldiallylammonium chloride, acrylamide, hydroxyethyl methacrylate, photoinitiator, and deionized water is (16-20): (7-10): (13-18): (3.5-6): (300-500); The photoinitiator includes phenyl (2,4,6-trimethylbenzoyl) phosphate lithium salt.

9. A magnetic therapy fabric containing heat-generating nylon fibers prepared by the method for preparing a magnetic therapy fabric containing heat-generating nylon fibers as described in any one of claims 1 to 8.

10. Use of the magnetic therapy fabric containing heat-generating nylon fiber as claimed in claim 9 in textiles.

Citation Information

Patent Citations

  • Chinlon fiber with magnet therapy health care function and preparation method thereof

    CN108385190A

  • Far-infrared heating, weather-resistant graphene nylon yarn and its preparation process

    CN111778581B

  • Graphene fiber and preparation method thereof

    CN109056118A

  • Graphene magnetic fiber and preparation method thereof

    CN114000220A

  • Preparation method of high-efficiency far-infrared heating polyamide 6 fiber

    CN117684284A